Relevance of the Problem of Myopia in School-age Children with Signs of Undifferentiated Connective Tissue Dysplasia - V. V. Li; G. P. Smoliakova; V. V. Egorov; O. I. Kashura (Oftalʹmologiâ, 2018)
Purpose: to study the frequency and structure of undifferentiated connective tissue dysplasia (UCTD) in school-age children with myopia, their relationship to choroidal thickness and course of myopia.Patients and methods. The object of study was 120 children (240 eyes) aged 11–13 years with school axial myopia (axial length (AL) from 24.5 to 26.0 mm). Special ophthalmological examination included optical coherent tomography of macular zone (“RTVue 100” Optovue, USA) and “Cross Line” scan for measuring choroidal thickness in foveal area and 1000 μm from it in nasal and temporal regions.Results. According to studies, the phenotypic signs of UCTD were diagnosed in 56 children (46.7%) with school myopia, the largest group included phenotypic signs of locomotor syndrome; 14 children (25%) had a weak degree of UCTD, 34 children (60.7%) — moderate degree and 8 children (14.3%) — pronounced degree. Comparative characteristic of changes in choroidal thickness detected a high degree of interrelation between the severity of clinical manifestations of UCTD and the level of decrease in blood-flow in the choroid. In children of the main group with signs of UCTD, the annual growth of AL exceeded the same parameters in children of the control group by more than 2.5 times (p < 0.05); due of accumulation of phenotypic signs of UCTD, a more noticeable tendency to decrease of choroidal thickness and the increase of AL was observed (p < 0.05). The statistical analysis confirmed the presence of significant negative correlation between the decrease in average thickness index in segment of the macular map and the degree of increase of AL (p < 0.05).Conclusions. According to results of diagnostic screening, in 46.7% children with school myopia, we detected phenotypic signs of UCTD. The method of optical coherence tomography showed that with increasing severity of UCTD, indexes of choroidal thickness in the macular zone are significant decreased. In the catamnesis (duration 1 year), it was found that in children with myopia with moderate and pronounced degrees of UCTD, increase of AL is associated with degree of thinning choroidal thickness, which indicates violations of biomechanical status of sclera.